A superior Li2SiO3-Composited LiNi0.5Mn1.5O4 Cathode for High-Voltage and High-Performance Lithium-ion Batteries. (1st May 2017) - Deng, Yunlong; Mou, Jirong; Wu, Huali; Jiang, Na; Zheng, Qiaoji; Lam, Kwok Ho; Xu, Chenggang; Lin, Dunmin
Graphical abstract: Abstract: In this work, Li2 SiO3, a layer-structured fast Li + -ion conductor with three-dimensional Li + paths, has been firstly introduced into LiNi0.5 Mn1.5 O4 to form novel cathode composites of (1-x)LiNi0.5 Mn1.5 O4 ·xLi2 SiO3 via a citric acid-assisted sol-gel method. The effects of Li2 SiO3 on the phase structure, morphology and electrochemical performance of the materials were investigated. As x increases, the structure and electrochemical properties of the materials are tailored. The cathode material with x = 0.10 delivers ultrahigh initial discharge capacity ∼150.3 mAh g −1, which is 24.4% larger than that of the pristine LiNi0.5 Mn1.5 O4 (120.8 mAh g −1 ). The Li2 SiO3 -composited LiNi0.5 Mn1.5 O4 materials present an enhanced cycling stability, better rate performance and lower charge transfer resistance. These excellent electrochemical properties indicate that the compositing of fast Li + -ion conductor Li2 SiO3 is an effective method to enhance the electrochemical performance of LiNi0.5 Mn1.5 O4 -based cathode materials.